TEMPERATURE MEASUREMENT AND CALIBRATION PADA ARMFIELD TH 1: PROPERTI TERMOMETRIK DAN RESPON SENSOR TEMPERATUR - Kevin Juniar; Steven Darmawan (POROS, 2021)
Calibration is needed to ensure that the measuring instrument works according to existing standards. The ability to calibrate measuring instruments is very necessary in the engineering world, especially calibration of temperature measuring instruments due to the importance of measuring temperature in the field of mechanical engineering. The purpose of this practical work report is to operate the Armfield TH1-Temperature Measurement and Calibration tool properly, investigate the thermometric properties of various temperature measuring instruments, also determine the response received by the device to changes in temperature. In testing the thermometric properties, using PT100 REF as a reference for other temperature measuring instruments. Thermistor Reading is the most accurate because it has the smallest difference with the PT100 REF compared to other measuring instruments. Thermistor Reading produces an average temperature difference of 0.036°C compared to PT100 REF. In testing the response of temperature sensors, the response given by the thermocouple temperature gauge is quite good both in the water bath and in the flask. When the thermocouple was transferred to the flask quickly, the temperature only ranged from 2.38°C to 4.05°C with a temperature change of 1.67°C, which means that the temperature measurement is quite stable when in the flask.